Positive Emotional Language in the Final Words Spoken Directly Before Execution - Hirschmüller, Sarah; Egloff, Boris (Frontiers in Psychology, 2016)
How do individuals emotionally cope with the imminent real-world salience of mortality? DeWall and Baumeister as well as Kashdan and colleagues previously provided support that an increased use of positive emotion words serves as a way to protect and defend against mortality salience of one’s own contemplated death. Although these studies provide important insights into the psychological dynamics of mortality salience, it remains an open question how individuals cope with the immense threat of mortality prior to their imminent actual death. In the present research, we therefore analyzed positivity in the final words spoken immediately before execution by 407 death row inmates in Texas. By using computerized quantitative text analysis as an objective measure of emotional language use, our results showed that the final words contained a significantly higher proportion of positive than negative emotion words. This emotional positivity was significantly higher than (a) positive emotion word usage base rates in spoken and written materials and (b) positive emotional language use with regard to contemplated death and attempted or actual suicide. Additional analyses showed that emotional positivity in final statements was associated with a greater frequency of language use that was indicative of self-references, social orientation, and present-oriented time focus as well as with fewer instances of cognitive-processing, past-oriented, and death-related word use. Taken together, our findings offer new insights into how individuals cope with the imminent real-world salience of mortality.